Hubungan Dukungan Keluarga dengan Kualitas Hidup Pasien DM di Puskesmas Kota Jambi - Rahmadhani, Dwi Yunita; Yesni, Marnila; Yuliana, Yuliana; M, Rino; Maimaznah, Maimaznah; Fajri, Jufri Al (Universitas Baiturrahim, 2024)
Family support is needed to improve the quality of life in type 2 DM patients. This study aims to identify the relationship between family support in terms of four dimensions (emotional, appreciation, instrumental and information) with the quality of life of type 2 DM patients at the Jambi City Health Center. The design in this study was cross-sectional analytic with a sample size of 120 patients with type 2 DM. Data analysis used Pearson's correlation coefficient, independent t-test and multiple linear regression. The results showed that the variables related to quality of life were age (p value 0.034; α 0.05), education (p value 0.001; α 0.05) and complications (p value 0.001; α 0.05). There is a relationship between family support in terms of four dimensions and quality of life (p value 0.001, α: 0.05). An increase in one family support unit will increase the quality of life by 35% after being controlled by education and DM complications. Nurses can increase family support with structured health education, facilitate the provision of family support as well as supervision and monitoring related to the application of family empowerment in providing nursing care to patients with type 2 DM